Bioavailability of two L‐thyroxine formulations after oral administration to healthy dogs. Issue 3 (26th February 2013) - Simpson, C; Devi, JL; Whittem, T
<x xml:space="preserve">Abstract</x> Objective To describe the pharmacokinetics of two veterinary formulations of L‐thyroxine available in Australia. Methods A two‐phase randomised, crossover, open‐label trial followed by a third‐phase parallel‐dosing trial was conducted in 11 healthy dogs with an investigative oral L‐thyroxine liquid formulation and a reference tablet formulation. Blood sampling was done at defined intervals and serum total L‐thyroxine concentrations were measured by radioimmunoassay. The post‐dose concentrations were plotted as a function of time for each period and the relative bioavailability of the two formulations were compared using a general linear model with factors for dog, phase, sequence and formulation. Results Following oral administration of the reference tablet at the dose of 100 μg/kg, a maximum plasma concentration of approximately 96.2 nmol/L (baseline endogenous corrected) was reached within 3.77 h. For the investigative liquid preparation at a dose of 50 μg/kg, the maximum plasma concentration was 60.1 nmol/L (baseline endogenous corrected), which was reached within 3.59 h. Conclusion The geometric mean of the relative bioavailability for the liquid/tablet product was 1.1, which suggests that the relative bioavailability of thyroxine following administration of tablet or liquid formulation is similar.